The Relative Effects of Logistics, Coordination and Human Resource on Humanitarian Aid and Disaster Relief Mission Performance - Idris, Aida; Soh, Saiful Nizam Che (UI Scholars Hub, 2014)
Most studies on humanitarian aid and disaster relief (HADR) missions suggest that the quality of logistics, coordination and human resource management will affect their performance. However, studies in developing countries are mainly conceptual and lack the necessary empirical evidence to support these contentions. The current paper thereby aimed to fill this knowledge gap by statistically examining the effects of the abovementioned factors on such missions. Focusing on the Malaysian army due to its extensive experience in HADR operations, the paper opted for a quantitative approach to allow for a more objective analysis of the issues. The results show that there are other potential determinants of mission success which deserve due attention in future studies. They also suggest that human resource is not easily measured as a construct, and that this limitation in methodology must be overcome to derive more accurate conclusions regarding its effect on HADR mission performance.